2022
DOI: 10.30773/pi.2022.0078
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperament on the Association Between Pre-treatment Anxiety and Chemotherapy-Related Symptoms in Patients With Breast Cancer

Abstract: Objective Pre-treatment anxiety (PA) before chemotherapy increases complaints of chemotherapy-related symptoms (CRS). The results on the association have been inconsistent, and the effect of temperament remains unclear. We aimed to determine whether PA is a risk factor for CRS and the effect of differing temperaments on CRS.Methods This prospective study comprised 176 breast cancer patients awaiting adjuvant chemotherapy post-surgery. We assessed CRS, PA, and temperament using the MD Anderson Symptom Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…Our results are in agreement with research using the Temperament and Character Inventory-Revised (TCI-R) test, which showed that some patients are typified by high Harm Avoidance (HA) and low Self-Directedness (SD) compared to a healthy control group ( Honorato et al, 2017 ; Öztürk et al, 2019 ; Choi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results are in agreement with research using the Temperament and Character Inventory-Revised (TCI-R) test, which showed that some patients are typified by high Harm Avoidance (HA) and low Self-Directedness (SD) compared to a healthy control group ( Honorato et al, 2017 ; Öztürk et al, 2019 ; Choi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, Profile 1 - “Low self-determination and pessimism,” highlighted the presence of a high HA and a low SD, which play an important role as indicators of poor avoidance of adverse stimuli, poor response to stressful conditions, and mood decline. Furthermore, they are indicators of poor adaptation to the disease condition and medical treatment ( Aukst Margetić et al, 2013 ; Choi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations